Futbol antrenörlerinin beslenme alışkanlıkları ve bilgi düzeylerinin belirlenmesi (İstanbul il örneği) - Yalçın, Zülal (My University, 2019)
Futbol Antrenörlerinin Beslenme Alışkanlıkları ve Bilgi Düzeylerinin Belirlenmesi ( İstanbul İl Örneği )ÖZET Amaç: İstanbul ilindeki futbol antrenörlerinin beslenme alışkanlıkları ile bilgi düzeylerinin tespit edilmesi ve bu konuda gerekli önerilerin yapılmasıdır. Gereç ve Yöntem: Teorik bilgilerle birlikte anket yöntemi uygulayarak antrenörlerin beslenme bilgi düzeyleri ve konuyla ilgili eğitim sonrası etkinin değerlendirilimiştir. Çalışma İstanbul ilinde Tüfad’a üye olan antrenörler ile sınırlıdır. Çalışma içerisinde beslenmenin futbol sporundaki önemi ve uygulamalardaki etkileri açıklanmıştır. Eğitimin başlangıcında ve bitiminde anket iki kez uygulanmıştır. Araştırma İstanbul İli Asya ve Avrupa Yakasında görev yapan 350 antrenöre uygulanmıştır. Araştırmada veri toplama aracı olarak, nicel veri toplama tekniklerinden faydalanarak antrenörlerin konuyla ilgili bilgilerine değerlendirilmiştir. Anketten elde edilen veriler bilgisayara aktarılarak istatistiksel çözümler için SPSS 22.0 (The Statistical Package for The Social Sciences) paket kullanılmıştır. Bulgular: Bireylerin beslenme eğitimi almadan önceki bilgi düzeyleri ile yaş grupları arasında önemli derecede anlamlı farklılık çıkmıştır(p<0,05). 36 ve üzeri yaş grubundaki bireyler diğerlerine göre daha düşük beslenme bilgisine sahiptirler. Bu durum 36 ve üzeri yaş grubundaki bireylerin beslenme bilgi düzeyleri üzerinde eğitimin faydalı olduğunu göstermektedir. Sonuçlar: Yaş ortalaması büyük olan antrenörlerin bilgilerinin daha çok tazenelnmesi çalıştıkları sporcularına daha rahat ışık tutacaklarını göstermektedir.

Determination of Nutritional Habits and Knowledge Levels of Soccer Coaches (Istanbul Province Case) ABSTRACT Purpose : Regulation of nutrition correctly and to meet the needs is one of the key factors in increasing the training and competition performance of the players, preventing injuries and using the conditional features more efficiently in the game. The competence of the coaches who communicate directly and continuously with the players is an issue that should be questioned. In this context, the aim of the study is to determine the nutrition habits and knowledge levels of football coaches in Istanbul and to make the necessary recommendations in this regard. Materials and Method: A survey was conducted by applying theoretical knowledge with the coaches after training on the subject of nutrition knowledge and influence değerlendirilimiştir.çalış on Istanbul Turkey Football Coaches Association in the province is limited by coaches who are members of the Association. In the study, the importance of nutrition in football sport and its effects on practices are explained. The questionnaire was administered twice at the beginning and at the end of the training. The research was applied to 350 trainers working in Asian and European sides of Istanbul. In the study, as a data collection tool, quantitative data collection techniques were used to evaluate the knowledge of the coaches. SPSS 22.0 (Statistical Package for the Social Sciences) program was used for statistical solutions. Findings: There was a significant difference between the knowledge levels of the individuals before the nutritional education and age groups (p <0.05). Individuals in the 36 and older age group have lower nutritional information than others. This indicates that education on nutritional knowledge levels of individuals aged 36 and over is beneficial. Conclusions: The more refreshing information of the coaches with an average age shows that they will shed light more easily to the athletes they work with.orts nutrition, football nutrition, football coach, coach nutrition, athlete nutrition.
Determination of nutritional habits and knowledge levels of soccer coaches (Istanbul province case)
Keywords: Antrenör beslenmesi; athlete nutrition; Beslenme; coach nutrition; football coach; football nutrition; Futbol antrenörleri; Futbol antrenörü; Futbolda beslenme; Nutrition; Soccer coaches; Sporcu beslenmesi; Sporda beslenme; Sports nutrition